Association of structural and psychological empowerment with depersonalization and personal accomplishment among nurses: A systematic review - Kulwadee Abhicharttibutra (2020)
© 2019, Thailand Nursing and Midwifery Council. All rights reserved. Burnout is a significant issue among nurses, and it impacts to the quality of care they provide. This systematic review evaluated the association between structural empowerment, psychological empowerment and two dimensions of burnout, depersonalization and personal accomplishment among nurses in the health care setting. Cross-sectional studies from 1990 to 2018 were searched from data bases of MEDLINE, CINAHL, EBSCO, ScienceDirect, Scopus, Springer Link, and Cochrane library, as well as unpublished studies and 35 eligible studies were found. After critical appraisal of their methodological quality, only 8 were included in the review. Cochran’s Q and I square statistic was used to test the heterogeneity. Meta-analysis results indicated a negative association between structural empowerment and depersonalization, and a positive association between structural empowerment and personal accomplishment. There was also a negative association between psychological empowerment and depersonalization, and a positive association between psychological empowerment and personal accomplishment. However, only 2-6 studies were combined in the meta-analysis for each outcome and they were of low to very low quality, so more primary studies need to be conducted to increase confidence in results and provide recommendations for policy and practice.